2016
DOI: 10.3389/fnins.2016.00509
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Ketone Body Oxidation Is Facilitated by a High Fat Diet Enriched with Advanced Glycation End Products in Normal and Diabetic Rats

Abstract: Diabetes mellitus (DM) causes important modifications in the availability and use of different energy substrates in various organs and tissues. Similarly, dietary manipulations such as high fat diets also affect systemic energy metabolism. However, how the brain adapts to these situations remains unclear. To investigate these issues, control and alloxan-induced type I diabetic rats were fed either a standard or a high fat diet enriched with advanced glycation end products (AGEs) (HAGE diet). The HAGE diet incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Therefore, the CSF βOHB level may be affected by MCT upregulation or inhibition, and a high level of plasma ketones may increase the protein expression of MCTs [2]. Iriki et al [7] found that the CSF βOHB level was 13% to 28% of the serum βOHB level in calves that received intraruminal administered of butyrate (11–44 g), while the value was 22% in the control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the CSF βOHB level may be affected by MCT upregulation or inhibition, and a high level of plasma ketones may increase the protein expression of MCTs [2]. Iriki et al [7] found that the CSF βOHB level was 13% to 28% of the serum βOHB level in calves that received intraruminal administered of butyrate (11–44 g), while the value was 22% in the control.…”
Section: Discussionmentioning
confidence: 99%
“…In ketone body metabolism, βOHB, the main component of ketone bodies, is carried by several MCTs across the blood-brain barrier [ 2 , 11 ] and used as an energy source by the brain and spinal cord during ketone body metabolism. Therefore, the CSF βOHB level may be affected by MCT upregulation or inhibition, and a high level of plasma ketones may increase the protein expression of MCTs [ 2 ]. Iriki et al [ 7 ] found that the CSF βOHB level was 13% to 28% of the serum βOHB level in calves that received intraruminal administered of butyrate (11–44 g), while the value was 22% in the control.…”
Section: Discussionmentioning
confidence: 99%